Herniotomy and its outcome in congenital inguinal hernia at a tertiary care hospital: descriptive study - Dhakne, Babasaheb S.; Beedkar, A. N.; Dalvi, Mayur R.; Bhalgat, Bhushan S. (International Surgery Journal, 2016)
Background:Herniotomy has been a standard mode of treatment for inguinal hernia which is a frequently encountered problem in children. It is considered to be easy to perform along with a good rate of success and low frequency of complications. Present study describes our experience with management of inguinal hernia in children by herniotomy with respect to operative procedure details and outcome at a government tertiary care referral centre in Aurangabad district of Maharashtra in India. Methods: The present prospective observational study was done between July 2014 and July 2016 at Surgery Department, Government Medical College and Hospital in Aurangabad district of Maharashtra state in India. 99 patients of age group 0-10 years diagnosed clinically as congenital inguinal hernia and managed by elective herniotomy were included in the study. Details like age at operation, type of anaesthesia, length of incision, whether superficial inguinal ring opened or not, whether sac was found or not, contents of sac, method and material used for skin closure, experience of operating surgeon, duration of hospital stay and complications were described. Results:In our study of 99 cases, 64 patients weight was between 9 - 16 kg. Most of the cases (89) were managed under general anaesthesia. Few cases among those aged above 5 years were operated under spinal anaesthesia (8) and caudal block (2). In 89 cases herniotomy was successfully done by 1 - 1.5 cm incision. In 10 cases we were required to extend our incision up to 2 cm or more. As in patients of 2 years or below age group, the superficial and deep rings are near to each other, in such cases we needed to open superficial ring. We have opened superficial ring in 8 cases. Content of the sac was omentum in most cases (87) whereas sac contained bowel in 5 cases. Subcuticular method of skin closure was used in most cases (72). Vicryl 3-0 suture material was used in most cases (85). 89 cases were operated by lecturers and senior surgeons of Surgery department whereas 10 cases were operated by doctors pursuing postgraduate course in surgery. Herniotomy is day care procedure but most of our patients (87) required 2 day stay in hospital. Reactive hydrocele was noticed in 22 cases and all of them resolved by second week. On the day of stitch removal, 6 patients were having pain while there was no patient with complaint of pain in second week. Conclusions:Thus, as per our study observations, herniotomy was a fairly effective procedure with no unresolved complications observed at the end of second week.